Skip to main content
$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# 9.2: Gram-Schmidt Orthogonalization

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

Suppose that $$M$$ is an $$m$$-dimensional subspace with basis

$\{x_{1}, \cdots, x_{m}\} \nonumber$

We transform this into an orthonormal basis

$\{q_{1}, \cdots, q_{m}\} \nonumber$

for $$M$$ via

1. Set $$y_{1} = x_{1}$$ and $$q_{1} = \frac{y_{1}}{||y_{1}||}$$

2. $$y_{2} = x_{2}$$ minus the projection of $$x_{2}$$ onto the line spanned by $$q_{1}$$.

That is,$y_{2} = x_{2}-q_{1}(q_{1}^{T}q_{1})^{-1}q_{1}^{T}x_{2} = x_{2}-q_{1}q_{1}^{T}x_{2} \nonumber$

Set $$q_{2} = \frac{y_{2}}{||y_{2}||}$$ and $$Q_{2} = \{q_{1}, q_{2}\}$$

3. $$y_{3} = x_{3}$$ minus the projection of $$x_{3}$$ onto the plane spanned by $$q_{1}$$ and $$q_{2}$$. That is,

$y_{3} = x_{3}-Q_{2}(Q_{2}^{T}Q_{2})^{-1}Q_{2}^{T} x_{3} = x_{3}-q_{1}q_{1}^{T}x_{3} \nonumber$

Set $$q_{3} = \frac{y_{3}}{||y_{3}||}$$ and $$Q_{3} = \{q_{1}, q_{2}, q_{3}\}$$. Continue in this fashion through step (m)

• (m) $$y_{m} = x_{m}$$ minus its projection onto the subspace spanned by the columns of $$Q_{m-1}$$

$y_{m} = x_{m}-Q_{m-1}(Q_{m-1}^{T}Q_{m-1})^{-1}Q_{m-1}^{T} x_{m}x_{m}- \sum_{j=1}^{m-1} q_{j}q_{j}^{T} x_{m} \nonumber$

Set $$q_{m} = \frac{y_{m}}{||y_{m}||}$$. To take a simple example, let us orthogonalize the following basis for $$\mathbb{R}^3$$

$\begin{array}{ccc} {x_{1} = \begin{pmatrix} {1}\\{0}\\{0} \end{pmatrix}}&{x_{2} = \begin{pmatrix} {1}\\{1}\\{0} \end{pmatrix}}&{x_{3} = \begin{pmatrix} {1}\\{1}\\{1} \end{pmatrix}} \end{array} \nonumber$

1. $$q_{1} = y_{1} = x_{1}$$
2. $$y_{2} = x_{2}-q_{1}q_{1}^{T}x_{2} = \begin{pmatrix} {0}&{1}&{0} \end{pmatrix}^T$$ and so, $$q_{2} = y_{2}$$
3. $$y_{3} = x_{3}-q_{2}q_{2}^{T}x_{3} = \begin{pmatrix} {0}&{0}&{1} \end{pmatrix}^T$$ and so, $$q_{3} = y_{3}$$

We have arrived at

$\begin{array}{ccc} {q_{1} = \begin{pmatrix} {1}\\{0}\\{0} \end{pmatrix}}&{q_{2} = \begin{pmatrix} {0}\\{1}\\{0} \end{pmatrix}}&{q_{3} = \begin{pmatrix} {0}\\{0}\\{1} \end{pmatrix}} \end{array} \nonumber$

Once the idea is grasped the actual calculations are best left to a machine. Matlab accomplishes this via the orth command. Its implementation is a bit more sophisticated than a blind run through our steps (1) through (m). As a result, there is no guarantee that it will return the same basis. For example

>>X=[1 1 1;0 1 1 ;0 0 1];

>>Q=orth(X)

Q=

0.7370  -0.5910  0.3280

0.5910   0.3280 -0.7370

0.3280   0.7370  0.5910

This ambiguity does not bother us, for one orthogonal basis is as good as another. Let us put this into practice, via (10.8).